Core outcome sets in women's and newborn health: a systematic review - Duffy,JMN; Rolph,R; Gale,CRK; Hirsch,M; Khan,KS; Ziebland,S; McManus,RJ (BJOG: An International Journal of Obstetrics and Gynaecology, 2017)
BackgroundVariation in outcome collection and reporting is a serious hindrance to progress in our specialty, over eighty journals have come together to support the development, dissemination, and implementation of core outcome sets.ObjectiveThis study systematically reviewed and characterised registered, progressing, or completed core outcome sets relevant to women's and newborn health.Search strategySystematic search using the Core Outcome Measures in Effectiveness Trial initiative and the Core Outcomes in Women's and Newborn Health initiative databases.Selection criteriaRegistry entries, protocols, systematic reviews, and core outcome sets.Data collection and analysisDescriptive statistics to describe characteristics and results.ResultsThere were 46 core outcome sets in maternal and newborn health, with the majority registered in 2015 (22; 48%) or 2016 (16; 35%). Benign gynaecology (5; 11%) and newborn health (3; 9%) is currently under-represented. Twenty-four (52%) core outcome sets were funded by international (1; 2%), national (18; 39%), and regional (4; 9%) bodies. Seven protocols were published. Twenty systematic reviews characterised the inconsistency in outcome reporting across a broad range of relevant healthcare conditions. Four core outcome sets were completed: reconstructive breast surgery (11 outcomes), preterm birth (13 outcomes), epilepsy in pregnancy (29 outcomes), and maternity care (48 outcomes). The quantitative, qualitative, and consensus methods used to develop core outcome sets have varied considerably.ConclusionsCore outcome sets are currently being developed across women's and newborn health, although coverage of topics is variable. Development of further infrastructure to develop, disseminate, and implement core outcome sets is urgently required.